Frugal innovation capabilities: conceptualization and measurement. (1st September 2021) - Shivdas, Avinash; Barpanda, Saswata; Sivakumar, Soumya; Bishu, Ram
Abstract : Firms in emerging markets are rapidly developing frugal innovation capabilities (FICs) in order to harness the growth potential of these markets. Researchers have explored this frugal innovation phenomenon through case studies of such firms. This nascent domain of study has been growing, and the demand for a specialized focus on FICs and their measurement is strong. This paper aims to satisfy the demand by conceptualizing FICs using the theoretical framework of dynamic capability, developing a measurement scale, and empirically validating the scale to measure FICs. Data from the medical device and automobile sectors in India were applied for this purpose. It is proposed that FICs are a composite variable with four dimensions: value for money, acceptable quality, scalability and marketability. The confirmatory factor analysis results validate these dimensions, presenting a gateway to explore FICs and their applications.